Co2-ch4 reforming over lanthanide promoted cobalt/mesoporous alumina catalyst for syngas production - Mahadi, Bahari (2021)
CO2-CH4 reforming has caught significant attention since this technology is able to convert undesirable ozone-depleting gases, CO2 and CH4, as feedstocks into the desired equimolar syngas for Fisher-Tropsch synthesis. At present, there is still a challenge in developing the highly stable and active catalysts for CO2-CH4 reforming as well as better resistance to carbon deposition. Therefore, the main idea of our work is to synthesize mesoporous alumina (MA) support using self-assembly hydrothermal approach (SAHA) technique before being impregnated with cobalt (Co). Then, the relationship between operating parameters, such as reforming temperature (923–1073 K) and reactant partial pressure (10-40 kPa) on catalytic performance and coke formation was evaluated in this work. The effect of lanthanide promoters (lanthanum (La), cerium (Ce), yttrium (Y), and samarium (Sm)) and promoter loading (1, 2, 3, and 5wt.%) on the physicochemical properties of 10%Co/MA catalyst was also studied in this project. 10%Co/MA exhibited great catalytic performance (CH4 conversion = 70.9%, CO2 conversion = 71.7% and Rate of deactivation = 1.3%), credited to the well dispersed Co within pore MA, strong metal-support interaction, and MA confinement ability. The Co particle dispersion on MA support evidently improved after promoter incorporation, resulting in smaller crystallite size and lesser Co agglomeration. The reactant conversions improved in the order of YCo/MA > LaCo/MA > CeCo/MA > SmCo/MA > Co/MA, while the amount of carbon deposit was recorded with the sequence of Co/MA > SmCo/MA > LaCo/MA > CeCo/MA > YCo/MA. Additionally, YCo/MA catalyst attained the highest catalytic performance (CH4 conversion = 85.8%, CO2 conversion = 92.2%, Rate of deactivation = 0.57%) and possessed the lowest carbon deposition (7.02%) due to great Co dispersion, small Co particle size with strong Co-MA interaction and higher oxygen storage capacity. H2/CO ratios were obtained within 0.78-0.86, which is slightly lower than 1 due to the reverse water-gas shift. A superior catalytic performance was shown by 3wt.% Y2O3 loading (CH4 conversion = 85.8%, and CO2 conversion = 90.5%), followed by 2wt.% > 5 wt.% > 1wt.% > 0 wt.% Y2O3 loading. This result was attributed to the favorable catalytic properties of 3%Y-10%Co/MA including small Co particle size, high Co dispersion, high amount of atomic ratio (Co/Al), and a high number of lattice oxygen vacancies. The excess Y2O3 addition (>3 wt.%) led to inevitably blocked Co active sites and resulted in decreasing catalytic performance. The 3wt.% Y2O3 promoter loading recorded the lowest carbon deposited (7.0%) due to the highest oxygen vacancies (78.1%) as compared to 1, 2 and 5 wt.% Y2O3. As a conclusion, the employment of MA support and incorporation of Y2O3 (3wt.) effectively boosted the Co performance in CO2-CH4 reforming along with suppressing the deposition of carbon on the catalyst surface as compared with other promoted catalysts (Ce, La, and Sm) and Y2O3 loadings (1, 2, 5wt.) owing to the improvement in catalysts structure and physicochemical attributes.